Development Strategy of Public Safety Engineering Science and Technology in the Next 20 Years - Tao Chen; Lida Huang; Yang Chen; Hongyong Yuan; Weicheng Fan (中国工程科学)
Safety is the basis of human survival and development. Building a higher level of Peaceful China is crucial for achieving high-quality development in the new stage. This study aims to look forward to the long-term goals by 2040, thus to support the conception of development strategies as well as the deployment of engineering science and technology projects for the construction of public safety. Considering the new situations and technologies, this study analyzes the development status and the state-of-the-art level of public security science and technologies worldwide. Focusing on the aspects of natural disaster prevention, accident disaster prevention, safe and resilient cities, and comprehensive emergency management, this study analyzes the development needs of public safety science and technologies in China. Based on this, it proposes the idea, strategic objectives, and an overall framework for the development of public safety science and technologies in China and summarizes the development directions, covering key engineering tasks, basic research directions, and major engineering projects. With regard to the path of scientific and technological development in the field of public safety in China, development proposals are made in terms of policy and research systems.